Menyiapkan Peserta Didik untuk Masyarakat 5.0 melalui Creative Responsibility Based Learning - Suyidno, Suyidno; M, Abdul Salam; Arifuddin, Muhammad; Misbah, Misbah; Siswanto, Joko (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2020)
Scientific creativity and responsibility are among the main competencies in the society 5.0, but they are not trained in school. Therefore, this study wants to produce a valid Creative Responsibility Based Learning (CRBL) to prepare students for society 5.0. This research is part of the educational research design using the Tessmer model, but data collection is still at the stage of self-evaluation and expert validation. CRBL's instructional goals are science process skills, responsibility, and scientific creativity; and other impact is the competence of society 5.0. The design of CRBL phase includes: generating creative responsibility, organizing creative learning needs, guiding group investigations, actualizing creative responsibilities, evaluating and reflecting. Students can explore creative and imaginative ideas, design creative products, and create technology products. In addition, the three validators agreed that CRBL was valid to prepare them for society 5.0.